Variable Parotid Papillue and its Implication in Sialadenitis - Araújo, J. E. N.; Costa Neta, H. T.; Oliveira, J. D. P.; Pereira, F. E. L.; Cavalcanti, R. L. M.; Gomes, F. B.; Assis, T. O.; Oliveira, A. S. B. (Journal of Morphological Sciences, 2018)
Introduction Papillae are small conical bumps found on the skin or mucous membranes surfaces. In the mouth, the parotid papillae are responsible for expelling saliva from the parotid gland to its cavity. Sialadenitis is an inflammation that affects the salivary gland and/or its duct.Objectives To report a variable parotid papilla case and its implication in sialadenitis.Materials and Methods The research was performed at the Morphofunctional Sciences Laboratory of the Faculdades Integradas de Patos - FIP. We used a cadaveric hemiface from the anatomy laboratory and a digital caliper rule for the morphometric evaluations.Results The papilla found was located posterior to the 3rd molar. The distance from the variation to the most frequent location of the papilla (18.8 mm).Conclusion The variable papilla was located in the lower retromolar region, which increases the chances of developing parotid sialadenitis, expanding the theoretical basis for its clinical diagnosis.
Keywords: parotid papillae; anatomical variation; anatomy